Ephypitic Ferns (Pteridophyta) from Raung Mount Banyuwangi, East Java Indonesia - Fuad Bahrul Ulum; Dwi Setyati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
An investigation of epiphytic Pteridophytes diversity at Mount Raung, Banyuwangi, East Java Province, Indonesia, was carried out in 7 February 2015. As many as 11 Pteridophytes from 3 families had been identified based on their morphological chracteristic. Among them, four species of Family Aspleniaceae, including Asplenium confusum Tardieu & Ching, Asplenium nidus L., Asplenium salignum Blume, and Asplenium tenerumoides S.B.Andrews. Polypodiaceae include Leptochilus wrightii (Hooker & Baker) X. C. Zhang, Microsorum punctatum (L.) Copel., Pyrrosia bicolor ( Kaulf. ) Ching, and Schellolepis percussa (Cav.) Pic.Serm. Vittariaceae include Antrophyum formosanum Hieron., Vittaria ensiformis Sw., and Vittaria lineata (L.) Sm. which is the smallest specimen with less than 10 cm long.Keywords: Mount Raung, Pteridophyta, Epiphytic, Families.